OPPORTUNISTIC PREDATION ON MIGRATORY SWARMS OF APIS MELLIFERA LINNAEUS, 1758 (HYMENOPTERA, APIDAE) BY PIAYA CAYANA (LINNAEUS, 1766) (CUCULIFORMES, CUCULIDAE) (REMUNOM, 2025)
Predation is one of the main ecological processes responsible for population regulation and the structuring of biological communities. In Brazil, bees of the genus Apis represent a food resource exploited by several opportunistic predators, including both vertebrates and invertebrates. The present study reports the first documented record of predation on Apis mellifera by Piaya cayana (Cuculidae), a bird species widely distributed throughout the Neotropical region. The observation took place on September 23, 2025, during an avifaunal survey conducted in a rural area of Itapagipe, Minas Gerais State, Brazil. An adult P. cayana was observed capturing bees in flight during a migratory event of A. mellifera. Predation lasted approximately 10 minutes, during which dozens of bees were consumed without any significant aggressive response from the swarm. The high prey density associated with the vulnerability of migratory colonies may favor opportunistic events of this nature. Piaya cayana is known for its predominantly carnivorous diet, consisting mainly of insects and small vertebrates, and adjusts its foraging strategies according to local resource availability. This record expands the current knowledge on the trophic ecology of the species and highlights its dietary plasticity, demonstrating its ability to exploit novel food resources under conditions of prey abundance.